Spremenimo slabo prakso "dostavljanja" otrok v šolo - Sember, Vedrana (Šport (Ljubljana), 2019)
Changes in children's lifestyle also affect their motor abilities. One of them is daily transport that is physically (in)active. A representative sample of 1,102 pupils from the second and third cycles of primary school was used in the study of pupils' transport to school and back home as well as correlation of transport methods with the distance between their home and the school. We established that nearly one half of pupils travelled to school and back home in a physically active way. Regretfully, detailed analyses showed that this was true mainly for those pupils who lived in close vicinity of the school. Pupils stated that the major reason for their inactive way of travelling was the distance from their home to the school; however, we established that there was a group of pupils whose parents drove them to school by car and who, in the afternoon, returned home on foot. Most of these pupils live at such a distance from their school that could, if they travelled to school in a physically active way, provide them with a good opportunity to increase their overall daily physical activity, which is why we propose that schools introduce more measures to improve the current situation
Keywords: gibalna dejavnost; motor activity; pešačenje; physical activity; physical fitness; pot v šolo; school; sport; šole; šport; telesna dejavnost; telesna pripravljenost; walking